Public Relations Communication Strategy in Improving the Image of the Padang City Government Through Social Media - M. Gozy Ladriansya (GLOBAL SCIENTS PUBLISHER, 2024)
This research is about public relations communication strategies in improving the image of the Padang city district government through social media. In forming the image of an institution, public relations has a broad relationship. In its role as a connecting bridge, government public relations collects, processes and disseminates information related to programs or policies, activities and achievements achieved by institutions to institutional responses to responses, aspirations and opinions that develop in society. Through social media, the Padang city district government continues to strive to improve the positive image of the region. The objectives to be achieved from this research are to find out how the public relations strategy of the Padang city Regency government improves the image of Padang city Regency through social media and to find out what are the inhibiting factors of public relations in implementing communication strategies through social media to improve the image of Padang city Regency.This research uses a qualitative method with a descriptive type. Descriptive qualitative research tends to use analysis that is used to investigate, discover, describe, and explain the qualities or features of social influence. In this case the researcher will conduct a descriptive study of a phenomenon about how Padang city district public relations can enhance its positive image through social media. The subject in this study was public relations for the Padang city District by conducting interviews with 2 (two) informants. The results in this study indicate that the public relations of the Padang city district government continues to improve its positive image by providing information to the public about local government programs through social media which can make it easier for the local government to communicate with the community. Public Relations of Padang city district provides information using social media through Instagram, Facebook and Whats Aap and Youtube groups about program plans and the development of local government activities in a transparent manner to the public in order to get sympathy and a positive image. In addition, the local government public relations took advantage of the influence of several community leaders such as religious leaders, traditional leaders and youth leaders. The inhibiting factors for public relations in implementing communication strategies through social media to improve the image of Padang city Regency are the lack of response from the community, the limited media used, the proximity to residents who live in remote areas and the negative perceptions that exist in the community itself.